Konsep Pendidikan Asah, Asih, Asuh dalam Pedagogi Feminis dan Tantangannya di Indonesia - Sasiana Gilar Apriantika (Sosietas: Jurnal Pendidikan Sosiologi, 2024)
The development of the educational paradigm has brought changes and adaptations in the implementation of education, both globally and at the local level. One of the recent developments in the educational paradigm is feminist pedagogy. This article aims to explore how the principles of feminist pedagogy have emerged in the concept of Asah, Asih, Asuh education and the challenges of applying feminist pedagogy in the education system in Indonesia. The method used is a literature study that uses literature review from various sources in accordance with the field of study such as books, journal articles, and research results. This research results in a study that the concept of Asah which means educating which focuses on developing cognitive aspects, is relevant to the concept of feminist pedagogy to produce education that is not value-free. Where education needs to pay attention to the different conditions and characters of each actor, so as to produce contextual and conditioned education. Furthermore, Asih, means giving sincere affection to each other and developing good values in life. Where this concept is relevant to the main principles of feminist pedagogy to provide compassion-based education. Third is Asuh, an educational concept that emphasizes developing an independent personality. This concept is relevant to the principles of feminist pedagogy in the form of education based on empowerment, by maximizing every potential of students and teachers in ongoing learning.